ChemInform Abstract: Radical N‐Cyanation of Sulfoximine Through Acetonitrile C—CN Cleavage. Issue 14 (March 2016) - Hu, Weiming; Teng, Fan; Peng, Haibo; Yu, Jintao; Sun, Song; Cheng, Jiang; Shao, Ying
Abstract: The N‐cyanation also works well with guanidine (IVa) whereas benzophenone imine gives the target product in only low yield.